2003
DOI: 10.1016/j.cardiores.2003.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Complete dynamic repopulation of decellularized heart valves by application of defined physical signals—an in vitro study

Abstract: This study demonstrated the superiority of the hydrodynamic approach of cellular reseeding to replace decellularized porcine heart valves with ovine cells with almost complete preservation of extracellular matrix integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 33 publications
1
59
0
2
Order By: Relevance
“…It has become increasingly clear that the assumption that xenoantigens are likely to be cell-associated is not valid. Our findings further emphasize that treatment of unfixed xenogeneic tissues for tissue engineering applications must shift from a paradigm of "decellularization" to one of "antigen removal" [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26]. Current or future antigen removal or antigen masking treatments will need to account for both cellular and extracellular matrix antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly clear that the assumption that xenoantigens are likely to be cell-associated is not valid. Our findings further emphasize that treatment of unfixed xenogeneic tissues for tissue engineering applications must shift from a paradigm of "decellularization" to one of "antigen removal" [9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26]. Current or future antigen removal or antigen masking treatments will need to account for both cellular and extracellular matrix antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Because tissues are unfixed in this application, it is necessary to remove graft antigenicity prior to implantation. Numerous physical and chemical treatments designed to decrease the immunogenicity of unfixed xenogeneic biomaterials have been investigated [9,11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26]. These treatments have generally been characterized as tissue "decellularization", based on the assumption that antigens mediating an immune response to the graft would likely be cell-associated.…”
Section: Introductionmentioning
confidence: 99%
“…Other histological evaluations of decellularized bovine pericardium, which we did not include in this study, confirmed the efficacy of the method. Note that this result is not always obtained as was reported by SCHENKE-LAYLAND et al [30] who described "almost complete" decellularization in porcine valves treated by enzymatic digestion using tripsin.…”
Section: Discussionmentioning
confidence: 56%
“…These systems either apply mechanical loading in a wide physiological range, mimicking both systole as well as diastole, 9,15,32 or are characterized by simulation of the systolic or opening phase of the cardiac cycle. 17,31,35,42 However, the diastolic phase or closing phase represents the load bearing phase of the cardiac cycle, in which most strain is applied to the heart valve tissue. The positive effect of cyclic tissue straining on the developing construct has been demonstrated in recent studies.…”
Section: Introductionmentioning
confidence: 99%